Identification, Biological Activities and Biosynthetic Pathway of Dendrobium Alkaloids - Mou, Zongmin; Zhao, Yi; Ye, Fei; Shi, Yana; Kennelly, Edward J.; Chen, Suiyun; Zhao, Dake (Frontiers in Pharmacology, 2021)
Dendrobium is a genus of flowering plants belonging to the Orchidaceae family with more than 1,400 species. Many Dendrobium species have been used as medicinal plants in several Asian countries for thousands of years. Alkaloids were reported as the major biological markers due to their complex chemical compositions and various types. In this review, we summarized the structural types of alkaloids, their pharmacological activities, as well as the mechanisms of biological activities. More than sixty alkaloids were isolated and identified from the Dendrobium genus. Moreover, the pharmacological effects of Dendrobium alkaloids as hepatic lipid and gluconeogenesis regulation, as neuroprotection, and as anti-tumor, anti-inflammatory, anti-diabetes, and anti-virus factors were described. Besides, the total chemical synthesis of dendrobine is provided, while the biosynthetic pathway of dendrobine has been proposed based on the functions of associated genes. For applications of this invaluable herb, more researches on the extraction of biological markers from compounds are needed. Further confirmation of the proposed biosynthetic pathways is anticipated as well.